(untitled) (Revista de Medicina Clinica, 2023)
The hematogenous route is one of the most important routes of metastasis in most malignant neoplasms. A greater proportion of lung metastases arrive through this route and for this metastasis phenomenon to begin, the tumor cells must detach from the original tumor and cross the barrier formed by the epithelial and endothelial basement membrane. Anchoring glycoproteins, which act as mediators of surface receptors of tumor cells, are important in this process. After this, the release of proteinases and collagenases by the neoplastic cells occurs, causing the rupture of the basement membrane and thus its passage into the general circulation.